beta-Functionalized Push-Pull Porphyrin Sensitizers in Dye-Sensitized Solar Cells: Effect of pi-Conjugated Spacers - Ishida, Masatoshi; Hwang, Daesub; Zhang, Zhan; Choi, Yung Ji; Oh, Juwon; Lynch, Vincent M.; Kim, Dong Young; Sessler, Jonanthan L.; Kim, Dongho (WILEY-V C H VERLAG GMBH, 2015)
A series of new beta-functionalized push-pull-structured porphyrin dyes were synthesized so as to investigate the effect of the p-conjugated spacer on the performance of dye-sensitized solar cells (DSSCs). Suzuki-and Heck-type palladium-catalyzed coupling methodologies were used to obtain various beta-functionalized porphyrins and beta-benzoic acid (ZnPHn) and beta-vinylbenzoic acid (ZnPVn) derivatives from beta-borylated porphyrin precursors. Photophysical studies of the resulting porphyrins revealed a clear dependence on the nature of the beta linker. In particular, it was found that a beta-vinylene linkage perturbs the electronic structure of the porphyrin core; this is less true for a beta-phenyl linkage. Theoretical analyses provided support for the intrinsic intramolecular charge-transfer character of the beta-functionalized, push-pull porphyrins of this study. The extent of charge transfer depends on the nature of the beta-conjugated linkage. The photovoltaic performances of the cells sensitized with beta-phenylenevinylene ZnPVn exhibited higher power conversion efficiency values than those bearing beta-phenyl linkages (ZnPHn). This was ascribed to differences in light-harvesting efficiency. Furthermore, compared to the use of a standard iodine-based electrolyte, the DSSC performance of cells made from the present porphyrins was improved by more than 1% upon using a cobalt(II/III)-based electrolyte. Under standard AM 1.5 illumination, the highest efficiency, 8.2 %, was obtained by using cells made from the doubly beta-butadiene-linked porphyrin.